Panoramic imaging in immersive extended reality: a scoping review of technologies, applications, perceptual studies, and user experience challenges - Tukur, Muhammad; Jashari, Sara; Alzubaidi, Mahmood; Salami, Babatunde Abiodun; Boraey, Yehia; Yong, Sindy; Saleh, Dina; Pintore, Giovanni; Gobbetti, Enrico; Schneider, Jens; Fetais, Noora; Agus, Marco (Frontiers in Virtual Reality, 2025)
Panoramic imaging plays a pivotal role in creating immersive experiences within Extended Reality (XR) environments, including Virtual Reality (VR), Augmented Reality (AR), and Mixed Reality (MR). This paper presents a scoping review of the research on panoramic-based XR technologies, focusing on both static and dynamic 360° imaging techniques. The study analyzes 39 primary studies published between 2020 and 2024, offering insights into the technological frameworks, applications, and limitations of these XR systems. The findings reveal that education, tourism, entertainment, and gaming are the most dominant sectors leveraging panoramic-based XR, accounting for 28.21%, 25.64%, 23.08%, and 20.51% of the reviewed studies, respectively. In contrast, challenges such as high computational demands, low image quality and depth perception, and bandwidth and latency issues are among the critical limitations identified in 28.21%, 23.08%, and 15.38% of the studies, respectively. The analysis also explores the level of user interaction and immersion supported by these systems, specifically in terms of degrees of freedom (DoF). A majority of the studies (56.41%) offer 3DoF, which allows users to look around within a static position, while only 35.90% provide 6DoF, enabling full movement in space. This indicates that most panoramic XR applications currently support limited interaction, though 6DoF systems are being adopted in a notable portion of the reviewed work to enable more immersive experiences. The review further examines key perceptual studies related to user experiences, including visual perception, presence and immersion, cognitive load and attention distribution, and spatial awareness in panoramic XR environments. In addition, user experience challenges such as discrepancies in spatial and movement perception, along with cybersickness, are among the most commonly reported issues. The paper concludes by outlining future research directions aimed at addressing these challenges, optimizing system performance, reducing user discomfort, and expanding the applicability of panoramic-based XR technologies in fields such as healthcare, industrial training, and remote collaboration.